Efforts to Enhance Anthropological Insights on Sustainable Practices in Human-Environmental Interactions in Central Java - Fatma Sarie; Muhamad Ammar Muhtadi; Rully Fildansyah (Westscience Press, 2023)
This study employs a broad multidisciplinary approach to investigate the complex dynamics of human-environment interactions in Central Java. The close relationship between cultural behaviors, like customary ceremonies and indigenous knowledge systems, and the surrounding environment is made evident by ethnographic discoveries. The qualitative tales are supported quantitatively by ecological analyses, such as land use mapping and biodiversity assessments, which underscore the relationship between ecological health and cultural resilience. Workshops and participatory mapping are examples of community engagement activities that provide a forum for co-creating sustainable projects with nearby communities. The robustness of the results is ensured by the triangulation of data sources. The results' synthesis highlights the role that cultural practices have in forming sustainable habits and adds to the growing global conversation about the relationship between culture and ecology.